Про один з типів ранньоямних поховань Північного Надазов'я - Константинеску, Л.Ф.; Привалов, А.І. (Археологія, 1996)
Публікується нове грунтове поховання з басейну р. Кальміус і наводяться результати дослідження його матеріального комплексу. В 1985 г. вблизи известного поселения Раздольное на р. Кальмиус было открыто грунтовое коллективное погребение. Материальный комплекс позволяет связывать его с раннеямным слоем Раздольненского поселения. Однако, погребальный обряд указывает на другие культурные традиции. Синкретический характер погребения отражает сложные процессы, происходящие в позднем энеолите в Северном Приазовье. The ground collective grave was excavated in 1985 near the well-known settlement Razdolnoye on the banks of river Kalmius. The assemblage of findings permits attributing it to the early pit layer of Razdolnoye settlement. The burial ceremony, however, outlines other cultural traditions. The syncretic character of the burial place shows complex processes which occurred in the late eneolithic period in the northern Azov Sea territories.